1991
DOI: 10.1161/01.cir.84.1.350
|View full text |Cite
|
Sign up to set email alerts
|

Protection against infarction afforded by preconditioning is mediated by A1 adenosine receptors in rabbit heart.

Abstract: We conclude that adenosine released during the preconditioning occlusion stimulates cardiac A1 receptors, which leaves the heart protected against infarction even after the adenosine has been withdrawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
536
2
24

Year Published

1993
1993
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,258 publications
(573 citation statements)
references
References 20 publications
9
536
2
24
Order By: Relevance
“…Indeed, it has been proposed that the cardioprotective effects of ischaemic preconditioning are secondary to the release of endogenous mediators such as adenosine (Liu et al, 1991;Thornton et al, 1992) which, via the stimulation of G protein-coupled (Gq/Go) receptors and activation of PKC, ultimately leads to the long-lasting opening of KATP channels. Similarly, the reductions in infarct size caused by E-type prostaglandins, such as PGEI, and by endothelin-l are due to the activation of KATP channels, as the cardioprotective effects of these autacoids are attenuated by glibenclamide and 5-HD (Hide et al, 1995a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been proposed that the cardioprotective effects of ischaemic preconditioning are secondary to the release of endogenous mediators such as adenosine (Liu et al, 1991;Thornton et al, 1992) which, via the stimulation of G protein-coupled (Gq/Go) receptors and activation of PKC, ultimately leads to the long-lasting opening of KATP channels. Similarly, the reductions in infarct size caused by E-type prostaglandins, such as PGEI, and by endothelin-l are due to the activation of KATP channels, as the cardioprotective effects of these autacoids are attenuated by glibenclamide and 5-HD (Hide et al, 1995a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, it is the most powerful form of cardiac protection known and it has been demonstrated in cardiac myocytes [2][3][4][5], intact hearts [6,7] and many animal species [8][9][10][11], including humans [12][13][14]. Downstream signalling molecules reported to be involved in PC include ATPdependent potassium channels [4,12,15,16], PKC (protein kinase C) isoenzymes [2, 3,12,15,17,18], MAPK (mitogen-activated protein kinase) enzymes [19][20][21], tyrosine kinases [22][23][24], PI3K (phosphoinositide 3-kinase) [22,25], heat-shock proteins [5,16,26], nitric oxide [27][28][29], free radicals [21,25,30] etc.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that Gi protein-coupled receptors mediate the cardioprotection of IPC (Liu et al, 1991;Schultz et al, 1998). The kappa opioid receptor (k-OR) is one of the receptors that mediate the cardioprotection of IPC (Wang et al, 2001a) and the action of its stimulation is mediated via a pertussis toxin-sensitive G-protein (Sheng et al, 1997).…”
Section: Introductionmentioning
confidence: 99%